2002
DOI: 10.1253/circj.66.305
|View full text |Cite
|
Sign up to set email alerts
|

Infected Papillary Fibroelastoma Attached to the Atrial Septum.

Abstract: rimary tumors of the heart are rare and are often classified histologically as 'benign'. One-sixth of these are papillary fibroelastomas, which usually originate in the heart valves. 1 A few previous reports have shown papillary fibroelastomas arising from the mural endocardium of the heart chambers, papillary fibroblastomas attached to the atrial septum are extremely rare. 2 Case ReportA 61-year-old woman was in good health until 2 months prior to admission to the Yamamoto General Hospital in June 1998. On ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…2 They can occur anywhere in the heart, but approximately 80% occur on the valvular endocardium 2 and can be associated with mechanical valve thrombus 3 and infection. 4 According to Howard et al, 55% of these tumors are found on the mitral or aortic valves, 1 they are usually singular, and only 7 cases of multiple tumors have been published in the literature. [5][6][7][8][9][10][11] The etiology of these tumors is unknown, but reaction to mechanical trauma, neoplasms, hamartomas or inflammatory nodules has been considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 They can occur anywhere in the heart, but approximately 80% occur on the valvular endocardium 2 and can be associated with mechanical valve thrombus 3 and infection. 4 According to Howard et al, 55% of these tumors are found on the mitral or aortic valves, 1 they are usually singular, and only 7 cases of multiple tumors have been published in the literature. [5][6][7][8][9][10][11] The etiology of these tumors is unknown, but reaction to mechanical trauma, neoplasms, hamartomas or inflammatory nodules has been considered.…”
Section: Discussionmentioning
confidence: 99%
“…2 The number of patients diagnosed with papillary fibroelastomas has increased since the advent of echocardiography, but cases of recurrence have not been reported and multiple occurrence is rare. [3][4][5][6][7][8][9][10][11] We present a case of double papillary fibroelastoma of the aortic valve with aortic regurgitation and mitral periprosthetic leakage occurring 4 years after resection of an initial left ventricular papillary fibroelastoma with mitral and tricuspid valvular disease. …”
mentioning
confidence: 99%
“…They are usually found on the atrial side on the atrioventricular valve and can be found on either side on semilunar valves. Papillary fibroelastomas attached to the atrial septum are rare 4,5 . In our case, the papillary fibroelastoma was attached to the left side of the interatrial septum.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, since atrial lipomas are now considered to be atrial fat infiltration and not neoplasms, fibroelastomas are likely the second most common cardiac neoplasm. Ninety percent are found on the valves, most commonly the aortic and mitral valves 4 . They are usually found on the atrial side on the atrioventricular valve and can be found on either side on semilunar valves.…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmia was reported in 16% of the paediatric patients with cardiac rhabdomyomas 1 ; of these, 6% presented with ventricular tachycardia. 1 Infective endocarditis has frequently been reported in association with cardiac tumours including cardiac myxoma [2][3][4] and fibroelastoma, 5,6 and the diagnosis of infected cardiac tumour was confirmed by histological examination of the surgically resected masses. [4][5][6] Other clinical features in our case are prolonged fever associated with persistent staphylococcus bacteremia after umbilical venous catheterisation.…”
Section: Discussionmentioning
confidence: 99%